(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The soft tissue is in close contact to the underlying skeletal hard tissue and takes up whatever form is dictated by the hard tissue. Yet, there exists some variations in cases of which, the soft tissue thickness varies in certain places to camouflage the skeletal deficiency. Hence, the purpose of this study was to evaluate the correlation of hard and soft tissue lower anterior facial height (LAFH) of different skeletal patterns on the south indian population. The study consisted of 30 lateral cephalograms, which were divided into three groups based on the skeletal relationship: Group A - Class I skeletal pattern, Group B - Class II skeletal pattern and Group C - Class III skeletal pattern. All the groups contained 10 radiographs each of that particular skeletal pattern. FACAD software was used to do the digital tracing and analysis. The obtained results were tabulated and were subjected to statistical analysis using SPSS software version 23. The results of Pearson’s correlation test revealed that Group A and Group B were positively correlated with statistical significance, whereas Group C was statistically insignificant. Hence, soft tissue LAFH can be used as a valuable indicator and an adjunct in diagnosis and treatment planning of orthodontic cases.